ABUJAMIN ROHAM'S DA'WAH METHOD IN FACING CHRISTIANIZATION IN INDONESIA - Lukman; Zaki Aqil Nashrullah (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2023)
Research Objective: Knowing Abujamin Roham's da'wah method in facing Christianization in Indonesia. Research Method: Qualitative. Research Results: Manhaj or da'wah method used by Abujamin Roham is divided into two categories, namely; (1) binȃan da'wah with the aim of fostering or building the Islam of the Indonesian Muslim community, among the da'wah carried out in this category are; writing about Islamogy and tausiyah/recitation, as well as silaturahim. (2) the proselytizing of dhifȃan with the aim of fortifying Muslims from the misguided enemies of Islam. Among his da'wah activities are; writing rebuttals, discussions or scientific debates and through the formation of the FAKTA Team. Conclusion: based on the results of analysis of research data, it can be concluded that Abujamin Roham's da'wah manhaj in the face of Indonesia's apostasy and Christianization efforts is da'wah through; :(1) Writing (2) Scientific discussion or debate (3) Silaturahim (4) Lecture, tausiyah or recitation (5) Formation of the FAKTA Team.